2012
DOI: 10.1148/radiol.12112074
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer: Missed Interval and Screening-detected Cancer at Full-Field Digital Mammography and Screen-Film Mammography— Results from a Retrospective Review

Abstract: To compare the percentages and mammographic features of cancers missed at full-field digital mammography (FFDM) and screen-film mammography (SFM) in women who participated in the Norwegian Breast Cancer Screening Program in 2002-2008. Materials and Methods: Social Science Data Services approval was obtained; the requirement for informed consent was waived. Cases were all the interval and screening-detected cancers from 35 127 FFDM and 52 444 SFM examinations in two Norwegian counties. Prior and diagnostic FFDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 22 publications
(31 reference statements)
4
63
2
4
Order By: Relevance
“…(9) Hoff et al reported similar screen-detected invasive cancer rates and interval cancer rates but higher screen-detected DCIS with digital compared to film. (16) Studies from Ireland, the Netherlands, and Norway (1719) have reported increased cancer detection rates with digital while studies from Spain, the United Kingdom, and the U.S. show similar cancer detection rates for digital and film. (2, 8, 1721)…”
Section: Discussionmentioning
confidence: 99%
“…(9) Hoff et al reported similar screen-detected invasive cancer rates and interval cancer rates but higher screen-detected DCIS with digital compared to film. (16) Studies from Ireland, the Netherlands, and Norway (1719) have reported increased cancer detection rates with digital while studies from Spain, the United Kingdom, and the U.S. show similar cancer detection rates for digital and film. (2, 8, 1721)…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have included interval-detected (nonscreening) breast cancer rates, because of the relatively small numbers of cases (9,14). Thus, no conclusions have been drawn regarding the potential benefit of FFDM versus SFM for decreasing the incidence of interval breast cancers.…”
Section: Breast Imaging: Transition From Screen-film To Full-field DImentioning
confidence: 99%
“…These studies indicate that 30-35% of the cancers diagnosed in the two-year interval following a screening, could be detected when reviewing the screening mammogram (i.e. were false negative) [148][149][150]. In comparison, approximately 20% of the screening-detected cancers could also be detected when the previous screening mammogram was reviewed and were false-negative.…”
Section: Discussionmentioning
confidence: 98%